An Airflow Output Control to Maintain a Constant Body Heat Loss During Sleep on Temperature-Changing Nights: Implementation in a Ventilated Sleep Capsule - Tomonori Sakoi; Masaki Kuroda; Yoshihito Kurazumi; Yoshihisa Takaoka; Kaori Narita; Sri Rahma Apriliyanthi (Buildings)
Good sleep is essential for a healthy life. While airflow improves sleep in a hot environment, it may cause an excessive drop in body temperature because thermal-adaptive behavior is inactive during sleep. This study aims to propose an airflow control theory that prevents the excessive drop in body temperature while maintaining good sleep. The theory changes the heat transfer coefficient between the skin and the environment by the intensity of the fan operation to maintain a heat loss of 30 W/m2 from a body with a skin temperature of 34.5 °C in a temperature-changing environment. We fabricated a ventilated sleep capsule in which this theory was embedded. Thermal manikin experiments were conducted to obtain the relationship between sensible heat transfer coefficients and the fan operating signal to establish control equations. We conducted a case study to evaluate whether the theory provided better sleep than sleeping with a regular fan running freely in homes in Ueda City, Japan, in one summer. Although the data used in the analysis were from only three subjects, the statistical analysis showed that sleeping in the ventilated sleep capsule provided better sleep, with a mean of 6% better sleep efficiency.